Plato's labyrinth :sophistries, lies and conspiracies in Socratic dialogues - Aakash Singh Rathore (Routledge, 2018)
This original and stimulating study of Plato's Socratic dialogues rereads and reinterprets Plato's writings in terms of their dialogical or dramatic form. Taking inspiration from the techniques of Umberto Eco, Jacques Derrida, and Leo Strauss, Aakash Singh Rathore presents the Socratic dialogues as labyrinthine texts replete with sophistries and lies that mask behind them important philosophical and political conspiracies.